Influence of some emulsifiers in the digestive stress of fats - García de la Puerta López, Pilar (Ars Pharmaceutica (Internet), 1965)
1. The aprición of a stress caused by a sudden change in the habitual fat of the diet is demonstrated that is pronounced by a significant diminution of the coefficient of digestibility of the fat. 2. That this phenomenon also occurs in rats adapted to butter when passing them to the diet with olive oil, than those who are accustomed to olive oil when feeding them with butter; that is, there is no specificity in the behaviour of the animals for one or another fat. 3. Through the action of the emulsifiers, this decrease in fat digestibility disappears, ie, these agents have an influence on the protection against stress. 4. In the case of olive oil and Tween-40 the physiological state of the animals (rats in the first phase of growth or adults) does not influence the action of the emulsifier. ...